Religious Moderation Practices in Indonesian Higher Education Institutions: A Systematic Literature Review on Typology, Strategy, and Evaluation - Moh. Saddad Muhibbi; Iksan; ⁠Mohd Faiz Mohd Yaakob; Sibawaihi; Sunariya Utama; Muhammad Fahmi (Jurnal Pendidikan Agama Islam, 2025)
Purpose – Various studies have explored religious moderation in Indonesian higher education in some aspects. However, these studies remain limited by the lack of an overview capturing the field’s overall development in terms of implementation and evaluation. Therefore, this study aims to map the implementation of religious moderation across Islamic and general Higher Education Institutions (HEIs), classifying the strategies employed and evaluations in diverse institutional contexts. Design/methods/approach – A systematic literature review (SLR) was conducted, examining high-quality Scopus-indexed articles published between 2019 and 2025 using the Watase Uake software. Articles were systematically screened using standard exclusion and inclusion criteria, with selected studies subjected to thematic analysis. Findings – 21 articles were selected from an initial pool of 217 studies. These studies covered 41 HEIs, comprising 27 Islamic and 14 general HEIs. Five main strategies for promoting religious moderation were identified: academic integration, the optimization of the House of Religious Moderation (RMB), Pesantren, Madrasah Diniyah, and institutional policy. These strategies were evaluated in the academic literature across multiple dimensions, focusing on student, lecturer, approach, content, and comparative analysis. Research implications/limitations – This study is limited by the lack of cross-institutional comparison of strategies and the absence of real-time data for evaluating religious moderation practices. Future research should address these gaps through empirical and comparative studies. Originality/value – The study provides practical guidance for HEIs that have not yet optimally implemented religious moderation, and for those seeking to enhance or expand their current practices. It highlights the importance of integrating both traditional and contemporary mechanisms to improve the effectiveness of moderation in HEI.